The Impact of Applying the Role Playing Method on Social Studies Lessons in Fourth Grade Student - Manan; Al-Rashiff Hamjilani Mastul (Journal of Pedagogy and Education Science, 2023)
This study aimed to determine the effect of the role-playing method on student learning outcomes in social studies. The subjects of this study were fourth-grade students who were grouped into experimental and control groups. Methods of data collection using observation, tests and documentation. The research instrument is the learning outcomes test's validity and the observation sheet's validity. The data analysis technique used is descriptive qualitative, and quantitative. The results showed a significant effect of learning methods on learning outcomes. Students who get the role-playing method get higher learning outcomes than student who takes lessons with various lectures. The results of observations on the affective domain in the experimental group were in the score range of 18.71 (high), and the control group was in the score range of 11.9 (low). The average increase in learning outcomes was 19.1 in the experimental group and 9.35 in the control group.